Single-cell analysis unravels the role of NK cells and monocytes in the control of SARS-CoV-2 breakthrough infections in vaccinated individuals - Huiwen Zheng; Jing Li; Xin Zhang; Yun Liao; Heng Li; Xin Zhao; Zihan Zhang; Jingjing Wang; Li Yu; Dandan Li; Heng Zhao; Haijing Shi; et al. (Human Vaccines & Immunotherapeutics)
Analyzing the antiviral response of natural killer (NK) cells and monocytes is essential to understanding vaccine protection in an immunized population facing SARS-CoV-2 variant breakthrough infections (BTIs). In this study, in peripheral blood mononuclear cells (PBMCs) from vaccinated individuals with SARS-CoV-2 infections, we observed an increase in adaptive CD57+NKG2C+ NK cells and classical monocytes (CMs). Single-cell sequencing analysis showed that the transcriptomic profiles of IFN-induced IFIT3 and other IFN-stimulated genes exhibited marked upregulation in NK cells, defined as CD56dimCD57+NKG2C+IFIT3+ NK cells. Additionally, CM in the blood showed characteristics indicative of differentiation into dendritic cells (DCs) and macrophages, which further evidenced their potential antiviral functions. Our study indicates that a vaccinated population rapidly activates an antiviral innate immune response following a BTI, thus revealing a link to the control of viral replication during SARS-CoV-2 BTIs.